New Insights and Knowledge on Cognition and Dementia from Population-Based Cohort of Older Adults in India. - Kenny, Rose (My University, 2020)
The Longitudinal Aging Study in India (LASI) is the world's largest aging survey, a groundbreaking nationally representative longitudinal survey to examine aging and retirement among India's aged 45 and older population. The importance of this study is reflected in the significant worldwide demographic change driven by lower fertility rates, increasing life expectancy, and subsequent aging of the population. This change will have far‐reaching implications in India where the population in 2019 was 1,38 billion and projected to increase to 1,7 billion by 2050. India is expected to surpass China as the most populated country in the world by 2027.1-3 The population aged 60 and older is projected to nearly double in the next 30 years from 10% in 2020 to 19% in 20504 with critical implications for public health, family dynamics and caregiving, and public policy.
PUBLISHED
Keywords: The Longitudinal Aging Study in India; 45 and older population; aging and retirement; The Longitudinal Aging Study in India; 45 and older population; aging and retirement; Ageing